Fa’amatai and the Land and Titles Court: Identifying Sites of Customary Authority in Contemporary Sāmoa - Morrison, William Iosefa Antonio (Victoria University of Wellington Law Review, 2023)
The 2020 Land and Titles Court (LTC) reforms in Sāmoa were a catalyst for the constitutional crisis that sent shockwaves through the Pacific. This article analyses what the debate surrounding these reforms, as well as the reforms themselves, reveal about fa’amatai (Sāmoa’s indigenous political system). Due to the reforms, LTC decisions can no longer be appealed to the Supreme Court, removing the ability for customary decisions to be balanced against constitutional individual rights. The debate around these reforms often hinged on whether constitutional rights impeded the exercise of customary authority. This article identifies the different hierarchical structures of customary authority in Sāmoa and articulates how they have evolved to accommodate the LTC and constitutional rights. It argues that, as fa’amatai has evolved to survive colonisation, the LTC itself and to some degree individual constitutional rights have come to form a core part of the fa’amatai today.